2020
DOI: 10.1039/d0ce01045f
|View full text |Cite
|
Sign up to set email alerts
|

Topological polymorphism and temperature-driven topotactic transitions of metal–organic coordination polymers

Abstract: Two metal-organic frameworks (MOFs) [Mg3(btdc)3(dmf)4]·DMF, (1) and [Mg3(btdc)3(dmf)4], (2) (H2btdc = 2,2´-bithiophen-5,5´-dicarboxylic acid; dmf = N,N-dimethylformamide) were synthesized from a similar reaction mixture at 80 °C or 130 °C, respectively....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 40 publications
1
5
0
Order By: Relevance
“…In turn, this leads to the change from a discrete anionic scandium complex to the layered coordination polymer. A similar trend is observed for the syntheses of CPs based on Co(II) and succinate, 47,48 Cd(II) and terephthalates, 49 Mg(II) and 2,2′-bithiophene-5,5′-dicarboxylate, 50 and Cd(II) and octafluorobiphenyl-4,4′-dicarboxylate. 51 Fluorine contacts play an important role in the crystal engineering of fluorine-containing materials.…”
Section: Synthesis and Comparison With Sc(iii) Terephthalate Mofssupporting
confidence: 79%
“…In turn, this leads to the change from a discrete anionic scandium complex to the layered coordination polymer. A similar trend is observed for the syntheses of CPs based on Co(II) and succinate, 47,48 Cd(II) and terephthalates, 49 Mg(II) and 2,2′-bithiophene-5,5′-dicarboxylate, 50 and Cd(II) and octafluorobiphenyl-4,4′-dicarboxylate. 51 Fluorine contacts play an important role in the crystal engineering of fluorine-containing materials.…”
Section: Synthesis and Comparison With Sc(iii) Terephthalate Mofssupporting
confidence: 79%
“…[78] It has been reported that the Mg 3 (RCOO) 6 building units can be linked by the linear 2,2′-bithiophen-5,5′-dicarboxylate (H 2 BTDC) ligand to synthesize two 3D MOFs with different structures via a temperature-controlled crystallization process. [79] As a result, the [Mg 3 (BTDC) 3 (DMF) 4 ]⋅DMF with a common pcu (low-temperature phase) and [Mg 3 (BTDC) 3 (DMF) 4 ] with a rare sxb (six-coordinated net, b type [80,81] ) (hightemperature phase) have been prepared by tuning the orientation of btdc 2anions under different reaction temperatures. Specifically, the [Mg 3 (BTDC) 3 (DMF) 4 ]⋅DMF and [Mg 3 (BTDC) 3 (DMF) 4 ] feature the parallel and semi-parallel arrangement of the btdc 2linkers, respectively.…”
Section: Mg-mofsmentioning
confidence: 99%
“…Compounds I and II have an identical formula of the coordination framework and are polymorphous modifications. A comparison of their crystallization conditions and structures shows a regularity often observed for other MOF: a lower synthesis temperature results in looser structures compared to those formed at higher temperatures, which lead, as a rule, to the formation of more compact phases with lower porosity [25][26][27]. Indeed, the low-temperature phase I has the crystallographic density of the framework ρ = 0.97 g/cm 3 and the pore volume equal to 56.7%, whereas the high-temperature phase II has the density ρ = 1.42 g/cm 3 and the pore volume equal to 31.8%.…”
Section: Resultsmentioning
confidence: 59%